The study of thermoelectric converter in the cooling system of the power equipment - A. V. Dmitriev; I. I. Valiev; O. S. Dmitrieva (Известия высших учебных заведений: Проблемы энергетики)
Replace power equipment in large quantities is extremely expensive. One possible way to increase the capacity of operating equipment is an organization of more intensive heat removal. The work of the thermoelectric converter in the cooling system investigated.